2022
DOI: 10.1002/eem2.12334
|View full text |Cite
|
Sign up to set email alerts
|

New Insight on Graphite Anode Degradation Induced by Li‐Plating

Abstract: Since the first lithium-ion batteries (LIBs) commercialized by Sony Corporation in 1991, they are being considered as the most suitable technology for electric vehicles and stationary energy storage systems. [1][2][3][4] Most of commercial LIBs are based on graphite anode due to their high energy density (high capacity of 372 mAh g −1 and low de-/lithiation potential around 0.1 V vs Li/Li + ), [5] long cycle life, low cost and environmental friendliness. [4,[6][7][8][9][10][11] With the motive to accelerate wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…From a materials perspective, strategic use of the empty spaces inside and between the particles of graphite is considered to be able to accommodate lithium metal and obtain a hybrid anode with high CE. ,, Given that graphite occupies a considerable volume and mass in the hybrid anode, its capacity contribution cannot be ignored. Although previous studies suggested that the structure and capacity retention ability of graphite may be compromised in hybrid anodes with long-term cycling, further direct evidence and comprehensive analysis are needed. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a materials perspective, strategic use of the empty spaces inside and between the particles of graphite is considered to be able to accommodate lithium metal and obtain a hybrid anode with high CE. ,, Given that graphite occupies a considerable volume and mass in the hybrid anode, its capacity contribution cannot be ignored. Although previous studies suggested that the structure and capacity retention ability of graphite may be compromised in hybrid anodes with long-term cycling, further direct evidence and comprehensive analysis are needed. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies suggested that the structure and capacity retention ability of graphite may be compromised in hybrid anodes with long-term cycling, further direct evidence and comprehensive analysis are needed. 20,25,26 In this contribution, we conducted in situ characterization of graphite during lithium metal plating and stripping. In the presence of lithium metal coating, the phase-transition process of graphite is hysteretic and mixed, and lithium ions cannot complete the reversible intercalation process under the "dead lithium" and SEI layers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) are widely used in electronics, public transportation, and energy storage based on their high energy and power density, long cycle life, and environmental friendliness. However, Li plating can easily lead to potential safety hazards, which is a problem that cannot be ignored. , Li plating occurs when lithium ions (Li + ) are reduced to metallic Li on the surface of the graphite anode during the charging process of the battery, which prevents normal intercalation. , Usually, poor battery balance, such as mismatched anode–cathode ratio (N/P) or manufacturing defects, and abuse of operating conditions, such as high C rate charging or low-temperature charging, will lead to Li plating. Li plating can lead to a reduction in the battery capacity and the formation of strong Li dendrites, which can puncture the separator and cause a short circuit, resulting in thermal runaway or even explosion. , Therefore, prevention of Li plating is essential for the safety and performance of LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In addition, as lithium is excessively deposited on the graphite surface, problems such as faster consumption of active lithium, cell short circuits, and fire due to dendrites may occur. [10][11][12][13][14][15][16] To achieve high energy density and stability, the composite electrode based on Si and graphite has been developed and utilized. Compared with pure Si, the mixture of graphite and Si shows higher electrical conductivity because the graphite surrounding Si compensates for the poor conductivity of Si.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7–9 ] In addition, as lithium is excessively deposited on the graphite surface, problems such as faster consumption of active lithium, cell short circuits, and fire due to dendrites may occur. [ 10–16 ]…”
Section: Introductionmentioning
confidence: 99%